Selektivität bei der Zuweisung erwerbsfähiger Hilfebedürftiger in Trainingsmaßnahmen oder zu privaten Vermittlungsdienstleistern - Sarah Bernhard; Joachim Wolff; Eva Jozwiak (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
– At the start of the year 2005 the Social Code II came into force in Germany. The reform introduced a unified means-tested benefit, the unemployment benefit II, for employable people who live in needy households. Prior to this reform they could have either received unemployment assistance benefit or (with little or no employment history) social benefit. A major goal of the reform is the integration of needy but employable people into the labour market. We regard two policies that aim at achieving this goal: (short-term) training programmes and the assignment to private placement services. The study relies on a large administrative data set of unemployment benefit II recipients. With probit models we investigate the individual determinants of the probability of entering from the unemployment stock at the end of January 2005 into each of these programmes in February 2005. We address the question whether people with particular problems of getting a job, like aged people or people without formal qualifications, are targeted by these policies. According to the new law all employable members of needy families should be activated. This includes partners of former unemployment insurance benefit recipients who did not participate in the labour market and are most likely hard-to-place. Our results do not suggest that the programmes generally target unemployed people who are particularly hard-to-place. This may be partly explained by the institutional set-up of the programmes. All programmes target young adults.
Keywords: 330; Arbeitslosengeld II-Empfänger; Trainingsmaßnahme; private Arbeitsvermittlung; schwervermittelbare Arbeitslose - Förderung; arbeitsmarktpolitische Maßnahme - Erfolgskontrolle